Comparison of continuous popliteal nerve blocks using lidocaine vs. bupivacaine infusions for ambulatory foot surgery: a randomized, double-blind, noninferiority trial - Echevarría, Ghislaine; Altermatt, Fernando R.; Miranda, Pablo; Araneda, Andrea; Corvetto, Marcia; de la Fuente, René; De la Cuadra, Juan C. (Frontiers in Anesthesiology, 2023)
Background and objectives: Continuous sciatic popliteal nerve block effectively manages pain after ankle and foot surgery. Most studies on continuous infusion of local anesthetics by perineural catheters have been made with bupivacaine, levobupivacaine, and ropivacaine, but lidocaine has not been used. The main objective of this study was to compare the quality of analgesia, motor function, and side effects between lidocaine and bupivacaine infusions in bilateral continuous popliteal nerve blocks for foot surgery.Methods: This was a prospective, double-blind, randomized, parallel-group, noninferiority study. We enrolled 70 patients undergoing bilateral foot or ankle surgery that could be performed under general anesthesia and continuous regional analgesia using sciatic popliteal nerve blocks. During their postoperative care, they were randomized into 2 groups: group lidocaine (lidocaine 0.5 %, 5 ml/h) or group bupivacaine (bupivacaine 0.1%, 5 ml/h), administered through elastomeric pumps.The primary outcome was pain at 24 hours after surgery, assessed by a verbal numeric rating scale (ranging from 0-10). A pre-specified non-inferiority margin of 1.5 was defined.Secondary outcomes were the degree of motor and sensitive block, total opioid use, and difficulties with pump or catheter management.Results: The mean postoperative pain at 24 hours of surgery was 2.06 (95% bootstrap confidence interval bCI 1.29, 2.83) and 1.82 (95% bCI 1.02, 2.62) in the lidocaine and bupivacaine group, respectively. The upper limit of the 95% bCI for the mean difference between lidocaine and bupivacaine was 0.82, declaring non-inferiority. No differences in the postoperative rescue analgesia use and satisfaction with care were found. No differences in postoperative NRS, sensory block and motor block were seen between groups.Conclusions: Lidocaine 0.5% and bupivacaine 0.1% provide similar postoperative analgesia through a sciatic popliteal catheter in ambulatory bilateral foot surgery patients.